The Resilience and the Practices of Teachers: The Case of Agsabo - Tasic, Shahani G. (RIRAI Publisher, 2025)
This qualitative case study explored the resilience and teaching practices of three teachers at Agsabo Elementary School, an Indigenous Peoples Education (IPED) school in Agusan del Sur. The participants, each with at least five years of teaching experience, were interviewed guided with interview schedules through in-depth, face-to-face sessions, each lasting up to two hours. The study aimed to address five key questions regarding teacher resilience, including definitions of resilience, strategies for engaging Indigenous learners, the impact of professional development programs, the role of administrative support, and the influence of learners, peers, administrators, and community interactions. The findings reveal that teachers at Agsabo define resilience manifested through patience and the ability to align and adapt their teaching strategies to societal and contextual needs of indigenous peoples (IP) learners. They utilized culturally accurate instruction, language preservation, and differentiated strategies to engage IP learners, building resilience through community observation and immersion. Professional development programs, particularly training on Canva and Evalbee, enhanced teachers’ resilience by improving classroom efficiency and boosting confidence in using technology. Administrative support, including financial aid, support for mental health and wellness, and proactive leadership, play a critical role in maintaining teacher well-being and sustaining effective teaching practices. Furthermore, interactions with learners, peers, administrators, and the community were found to significantly strengthen teachers' resilience and effectiveness, fostering motivation, improving instructional strategies, and aligning teaching with learners’ cultural backgrounds. These interconnected factors contribute to a supportive and effective teaching environment, highlighting the importance of comprehensive support systems for teacher resilience in an IPED school.